Pengaruh Foot Massage dan Pergerakan Sendi Ekstremitas Bawah terhadap Nilai Ankle Brachial Index (ABI) pada Pasien DM Tipe 2 di Wilayah Kerja Puskesmas Peukan Baro, Kab. Pidie - Isni Hijriana; Miniharianti Miniharianti (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Diabetes mellitus Type 2 (DM Type 2) is the risk factor for the incidence of vascular. Diabetic neuropathy and/or peripheral arterial disease, are common and represent major causes of morbidity and mortality in people with diabetes. Physical exercises is have been done to prevent from diabetes complication, and one of them is by foot massage and lower extremity joint movement. Measuring the value of ankle brachial index (ABI) is one of non-invasive actions to evaluate the risk for peripheral vascular in primary treatment. The objective of this research was to determine the influence of foot massage and joint movement exercise on ABI value in DM Type 2 patients. The research used quasi experiment method with pretest-posttest group design and two intervention groups. The samples were 40 DM Type 2 patients, taken by using consecutive sampling technique. Intervention was given by conducting foot massage and lower extremity joint movement exercise. Wilcoxon Signed Ranks statistic test showed that there was the difference in pre and post intervention of foot massage and lower extremity joint movement from ABI value, for (p=0.00). The conclusion was that foot massage and lower extremity joint movement exercise could increase ABI value if it was done continuously. It could also increase blood flow to artery. This research could bean input for nursing care to make physical exercises such as foot massage and lower extremity joint movement as prevention from risk of longterm Complications in DM Type 2 patients.